"Indigitado estrupício": arqueologia e significados acerca do muro do Forte do Presépio (Belém-Pará) - LOPES, Rhuan Carlos dos Santos (Universidade Federal do Pará, 2012)
During the years 1999 and 2002, the Fort of Nativity in Belém, Pará state, was the target of multidisciplinary research for its restoration and adaptation for its further musealization, according to “Feliz Lusitania” project. One of the sciences that are devoted to this research is the archeology, having a significant role in driving this project. During this process, a specific subject, which did not respect to archaeological research, took a great dimension: the overthrow of a wall that appeared between the street and fortification. In this context, the wall was considered a "phantasmagoria" that prevented the ancient symbiosis between the fortress and the city. However, the demolition of the wall was a decision made behind the backs of archeology team, but according to the aesthetic and functional interests of the museum plan. To justify this action, a series of assignments were given to that artifact ("Indignant conflict”, “aberration”, "freak"). This paper aims to discuss two aspects: (a) the meanings given to the wall, understood as an artifact capable of giving rise to "different ways of seeing and acting in the world", and (b) the effective positioning of the archeology facing the overthrow of the wall.